Conference – 1990 Equation

B t = C t + I t ( 1+ψ( I t / K t ) )+θ B t F( K t , L t ) K t = I t δ K t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGceaqabeaaceWGcb GbauaadaWgaaWcbaGaamiDaaqabaGccqGH9aqpcaWGdbWaaSbaaSqa aiaadshaaeqaaOGaey4kaSIaamysamaaBaaaleaacaWG0baabeaakm aabmaabaGaaGymaiabgUcaRiabeI8a5naabmaabaGaamysamaaBaaa leaacaWG0baabeaakiaac+cacaWGlbWaaSbaaSqaaiaadshaaeqaaa GccaGLOaGaayzkaaaacaGLOaGaayzkaaGaey4kaSIaeqiUdeNaamOq amaaBaaaleaacaWG0baabeaakiabgkHiTiaadAeadaqadaqaaiaadU eadaWgaaWcbaGaamiDaaqabaGccaGGSaGaamitamaaBaaaleaacaWG 0baabeaaaOGaayjkaiaawMcaaaqaaiqadUeagaqbamaaBaaaleaaca WG0baabeaakiabg2da9iaadMeadaWgaaWcbaGaamiDaaqabaGccqGH sislcqaH0oazcaWGlbWaaSbaaSqaaiaadshaaeqaaaaaaa@5F1A@